New non-drug technologies for lymphedema associated with breast cancer: a review - Tatiana V. Apkhanova; Tatiana V. Konchugova; Detelina B. Kulchitskaya; Olga V. Yurova; Elena M. Styazhkina; Tatyana V. Marfina; Lev G. Agasarov; Valeriia A. Vasileva; Elena S. Berezkina (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. Breast Cancer-Related Lymphedema (BCRL) is the most common complication after radical treatment of breast cancer (BC). Currently, there are no molecular therapeutic targets whose pharmacologic action could prevent edema, making it necessary to study the efficacy of non-pharmacologic techniques. AIM. To study the effectiveness of non-medication technologies in BCRL to develop recommendations for practical application based on the analysis of systematic reviews and meta-analyses of randomized controlled trials (RCTs). MATERIALS AND METHODS. The search was conducted in the Physiotherapy Evidence-Based Database (PEDro, 2002-2024) using the keywords: "lymphedema", "upper limbs", "breast cancer". A total of 203 sources were selected as of March 2024. RESULTS AND DISCUSSION. Numerous studies have found that the use of early postoperative physical exercise with a gradual expansion of the load in patients at risk of developing BCRL is a safe and effective method of rehabilitation. The effectiveness of early preventive use of manual lymphatic drainage (MLD) in 4 RCTs was studied in a Cochrane review. However, the clinical effectiveness of early prophylactic use of MLD to prevent BCRL remains insufficiently proven. In contrast, prophylactic use of compression sleeves has been shown to reduce and delay the onset of arm lymphedema in women at high risk of developing BCRL during the first year after breast cancer surgery. Studies have also confirmed the effectiveness of an early Prospective Surveillance Model using bioimpedance spectroscopy for early detection and immediate treatment of BCRL. It has been proven that in order to reduce the volume of a limb with BCRL, it is necessary to prescribe an intensive phase of complex decongestive therapy (CDT) for at least 3 weeks. Studies have also proven the effectiveness of using a standard or improved intermittent pneumatic compression device in the rehabilitation phases, including at home. CONCLUSION. To reduce the risk of development and progression of BCRL, modern exercise therapy techniques should be used to increase physical activity in order to control body weight, and educational techniques for self-massage and self-application of compression bandages should be actively used. The "golden" standard for conservative treatment of BCRL remains CDT, which is based on MLD. At the same time, the wider use and development of new methods of hardware lymphatic drainage that imitate MLD, which is a highly resourceful and costly method of treatment for BCRL, is justified. To confirm the clinical effectiveness of improved hardware pneumocompression, additional RCTs assessing long-term treatment results are required.